Ab initio calculation of electronic and magnetic properties of rare earth (Pm, Sm and Er)-doped CuO. (2022) - Salmani, E.; Syad, Badr Ait; Ez-Zahraouy, Hamid; Benyoussef, Abdelilah
Abstract: In this work, we study the electronic and magnetic properties of the semiconductor copper (II) oxide doped with three rare earths (RE = Pm, Sm and Er), Cu1−x REx O (x = 0.10) in the rutile structure. The presence of the 4f orbital in our structures imposes us to choose the local density approximation with Self-interaction-corrected (LDA-SIC) to improve the results obtained. Depending on the rare earths (RE) used, we discuss for each element the critical temperature extracted by using the mean field approximation (MFA).